Company Stores in the Donbas in the Late Nineteenth and Early Twentieth Century - Куліков, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The paper is about the history of company stores in the Donbas during the imperial industrialization. It demonstrates that company stores existed in the area from the emergence of company towns until the fall of the Russian Empire. The image about company stores as a means to exploit and enslave workers is based on the evidence from the initial period of the company towns’ history. After the mid-1880s, the labor legislation, labor movement, and free labor marked limited the endeavors of the enterprises to use this tool to make extra profit on their employees. Competition from other stores and mines in the same labor market held down the prices in the company stores. From the turn of the nineteenth century, prices at company stores were similar to those in the nearby independent stores, and the higher wages of workers might have compensated for the higher store prices around the isolated mines.